SHELF: Combination of Shape Fitting and Heatmap Regression for Landmark Detection in Human Face - Quyen, Ngo Thi Ngoc; Linh, Tran Duy; Phuc, Vu Hong; Nam, Nguyen Van (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2023)
Today, facial emotion recognition is widely adopted in many intelligent applications including the driver monitoring system, the smart customer care as well as the e-learning system. In fact, the human emotions can be well represented by facial landmarks which are hard to be detected from images, due to the high number of discrete landmarks, the variation of shapes and poses of the human face in real world. Over decades, many methods have been proposed for facial landmark detection including the shape fitting, the coordinate regression such as ASMNet and AnchorFace. However, their performance is still limited for real-time applications in terms of both accuracy and efficiency. In this paper, we propose a novel method called SHELF which is the first to combine the shape fitting and heatmap regression approaches for landmark detection in human face. The heatmap model aims to generate the landmarks that fit to the common shapes. The method has been evaluated on three datasets 300W-Challenging, WFLW, 300VW-E with 31557 images and achieved a normalized mean error (NME) of 6.67% , 7.34%, 12.55% correspondingly, which overcomes most existing methods. For the first two datasets, the method is also comparable to the state of the art AnchorFace with a NME of 6.19%, 4.62%, respectively.